The use of blood flow restriction training in an injured elite swimmer on swimming performance and hypertrophy - Morris, N. (Journal of Australian Strength and Conditioning, 2018)
The purpose of this study was to document the effects of Blood Flow Restriction (BFR) combined with low load resistance training on swimming performance and muscular hypertrophy following a three-week training period for an injured elite male swimmer. The subject was a 20 year old male swimmer with osteolysis in their left shoulder. The subject had 10 years` competitive experience and four years at Australian open nationals in multiple events.